Surakarta Creative Economy Development Model As an Effort to Create New Economic Resources - Nugroho, SP; Susila, Ihwan; Setyawan, Anton Agus (Jurnal Manajemen Dayasaing, 2018)
As a center of creative economy, Surakarta City has cultural diversity and creative people. This is reflected by the availability of resources and creative products in each sub-district to be further developed. The development of the creative economy of Surakarta will address the challenges of future economic development including increasing economic growth, reducing poverty, creating new jobs, and industrial competitiveness. This study aims to develop an integrated model of each stakeholder coordinated by the Regional Device Organization (RDO) in Surakarta government to support the implementation of the development of the national creative economy. The Surakarta creative economy development model refers to the 5 pillars of the development of the national creative economy. This development model has a relationship between the foundations and pillars of development, planning activities supported by stakeholders (academics, business, government, and communities), as well as markets for creative products. RDO programs and activities are prepared based on the pillars of creative economic development that are in line with the tasks and functions. The Department of Education focuses on programs and activities on the pillars of resources, creating creative people at the basic level through the school curriculum. The Department of Cooperative and MSME focuses on the pillars of resource development through training and business network development, as well as financial intermediation. Department of Industry and Labor focus on developing resources and institutions. The Department of Tourism and Culture focuses on industrial pillars. The Department of Trading focuses on industrial pillars.